Kinetics of Oxidation of n-Butanol by p-Methyl N-Bromobenzamide - Choubey, O.N.; Seeriya, V.K.; Awasthi, S.K. (Asian Journal of Chemistry, 2010)
Kinetic studies in the oxidation of n-butyl alcohol by p-methyl n-bromobenzamide has been made in aqueous acetic acid in the presence of mercuric acetate. The reaction is first order with respect to the oxidant and unity with respect to the substrate. The reaction is retarded by the initial addition of benzamide. The activation parameters have been calculated and a suitable mechanism has been proposed.